PENYUSUNAN STANDAR PELAYANAN MINIMAL JALAN NASIONAL - Adi Soelistijo; Prayoga Luthfil Hadi (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2019)
Abstract Road infrastructure is one component of land transportation and has an important role for the movement of people and goods and regional development. In its implementation, a minimum service standard is needed to ensure the level of service expected road users. In this study, the process of preparing minimum service standards for national roads was discussed. The preparation is carried out through several stages so as to produce a list of indicators and parameters that can be implemented for national roads in Indonesia. The list of indicators and parameters was obtained through collecting data from previous studies, regulations, best practices on the implementation of minimum service standards in other countries, as well as discussions with road operators, academics, and road users. The list of indicators and parameters is then validated by distributing questionnaires back to road operators, academics, and road users to be assessed quantitatively on the level of importance and ease of implementation. Data from respondents were then analyzed using quadrant analysis to obtain priority indicators and parameters proposed to be used in minimum service standards of national roads. Keywords: road infrastructure, national roads, minimum service standards, level of service  Abstrak Infrastruktur jalan merupakan salah satu komponen dalam penyelenggaraan transportasi darat dan memiliki peranan penting untuk pergerakan orang dan barang serta pengembangan wilayah. Dalam penyelenggaraannya, diperlukan suatu standar pelayanan minimal untuk menjamin tingkat pelayanan yang diharapkan oleh pengguna jalan. Pada kajian ini dibahas proses penyusunan standar pelayanan minimal untuk jalan nasional nontol. Penyu-sunan dilakukan melalui beberapa tahapan sehingga menghasilkan daftar indikator dan parameter yang dapat diimplementasikan untuk jalan nasional di Indonesia. Daftar indikator dan parameter tersebut diperoleh melalui pengumpulan data dari studi terdahulu, peraturan, best practice penerapan standar pelayanan minimal di negara lain, serta diskusi dengan penyelenggara jalan, akademisi, dan pengguna jalan. Daftar indikator dan parameter tersebut kemudian divalidasi dengan penyebaran kuesioner kembali ke penyelenggara jalan, akademisi, dan pengguna jalan untuk dinilai secara kuantitatif tingkat kepentingan dan kemudahan implementasinya. Data dari responden kemudian dianalisis menggunakan analisis kuadran untuk mendapatkan indikator dan parameter prioritas yang diusulkan untuk digunakan dalam standar pelayan minimal jalan nasional nontol. Kata-kata kunci: infrastruktur jalan, jalan nasional, standar pelayanan minimal, tingkat pelayanan